ORGANISASI KEAGAMAAN DAN KEAMANAN INTERNASIONAL: Beberapa Prinsip dan Praktik Diplomasi Nahdlatul Ulama (NU) Indonesia - Purwono, Andi (JPP (Jurnal Politik Profetik), 1970)
The current international security threat is not solely within the context of high politics. Conflict of communal identity has frequently become one of the real threats. Within this context, the treatment of state actors has not been sufficient. Diplomatic participation of private groups such as religious ones is getting more obvious. This article is particularly aimed at elaborating diplomatic efforts by Nahdhatul Ulama, one of the most influential Islamic organizations in Indonesia, in its contributions to establish worldly peace in both principles and practices.